Pecan Cultivars for North Florida - Peter C. Andersen (EDIS)
Pecan recommendations for Florida have been updated to include new information about cultivar performance. Check out this revised 13-page fact sheet to select the best cultivars for yield, performance, resistance to disease, and resistance to limb breakage. Written by Peter C. Andersen, and published by the UF Department of Horticultural Sciences, September 2011. (UF/IFAS Photo: Thomas Wright.)